2016
DOI: 10.29252/jnkums.7.3.645
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of qualitative and quantitative of antocyanines, carotenoids, flavonoids and antioxidant activity of methanol extract from aerial parts of Scutellaria pinnatifida A.Hamilt subsp alpina (Bornm) Rech.f

Abstract: ‫ﯿ‬ ‫ﺒﺎت‬ ‫دي‬ ‫آﻟﮑﺎﻟﻮﺋﯿﺪي‬ ‫و‬ ‫ﺗﺮﭘﻨﻮﺋﯿﺪي‬ ‫ﻧ‬ ‫ﯿ‬ ‫ﺰ‬ ‫ا‬ ‫از‬ ‫ﯾ‬ ‫ﻦ‬ ‫ﺟﺪاﺳﺎز‬ ‫ﺧﺎﻧﻮاده‬ ‫ي‬ ‫ﺷﺪه‬ ‫اﺳﺖ‬ ‫و‬ ‫ز‬ ‫ﺗﻌﺪاد‬ ‫ﺗﺎﮐﻨﻮن‬ ‫ﯾ‬ ‫ﺎد‬ ‫ي‬ ‫ﺗﺮﮐ‬ ‫ﯿ‬ ‫ﺒﺎت‬ ‫ﻓﻼوﻧﻮﺋﯿﺪي‬ ‫و‬ ‫آن‬ ‫ﻣﺸﺘﻘﺎت‬ ‫ﺑﯿ‬ ‫اﺛﺮات‬ ‫ﺑﺎ‬ ‫ﻫﺎ‬ ‫ﻮﻟﻮژ‬ ‫ﯾ‬ ‫ﮏ‬ ‫ﺷﺎﻣﻞ‬ ‫ﺗﻮﺟﻪ‬ ‫ﻗﺎﺑﻞ‬ ‫آﻧﺘ‬ ‫اﺛﺮ‬ ‫ﯽ‬ ‫اﮐﺴ‬ ‫ﯿ‬ ‫ﺪاﻧ‬ ‫و‬ ‫ﯽ‬ ‫ﺳ‬ ‫ﯿ‬ ‫ﺘﻮﺗﻮﮐﺴ‬ ‫ﯿ‬ ‫ﮏ‬ ‫ﮔﻮﻧﻪ‬ ‫از‬ ‫ﻫﺎي‬ ‫ﺟﻨﺲ‬ ‫ﺑﻪ‬ ‫ﻣﺘﻌﻠﻖ‬ ‫ﺷﺪه‬ ‫اﺳﺘﺨﺮاج‬ Freeman,1995; pp. 263-290. 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…The total carotenoids content of banana leaf was 12.8 ± 0.1 mg /g. It has been obtained in the otherstudies; (FEYZI et al, 2015). However, the total carotenoids content of Scutellaria pinnatifida as 3.52 ± 0.56 which was much lower than the present study.…”
Section: Resultscontrasting
confidence: 66%
“…The total carotenoids content of banana leaf was 12.8 ± 0.1 mg /g. It has been obtained in the otherstudies; (FEYZI et al, 2015). However, the total carotenoids content of Scutellaria pinnatifida as 3.52 ± 0.56 which was much lower than the present study.…”
Section: Resultscontrasting
confidence: 66%
“…Since the color did not change, it was concluded that the pistachio extract does not contain anthocyanins. [85][86][87][88]…”
Section: Anthocyanins Diagnosis Testmentioning
confidence: 99%